Analisis Variasi Jenis Perekat Tetes Tebu dan Tepung Tapioka Pada Pemanfaatan Limbah Ampas Tebu Menjadi Briket - Mufti, Aulia Annas; Akram, Muhammad; Lisafitri, Yuni; Kurnianingtyas, Erlina (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2024)
Energy is a factor that has a very important role in various economic activities and people's lives. The availability of energy and fuel oil is currently lacking, indicating the need to switch to alternative fuels, one of which is charcoal briquettes. Sugarcane bagasse is one of the many biomasses that can be used. as a raw material for making briquettes. The process of making charcoal briquettes requires additional material in the form of an adhesive whose purpose is to glue the charcoal powder so that it becomes a solid form. As a binder for briquettes, molasses has the potential to increase the calorific value because it is rich in carbon content derived from sucrose which is abundant in molasses. Therefore, a study was conducted to analyze the fuel characteristics of bagasse briquettes with adhesive variations in the form of tapioca flour and molasses. The parameters to be tested are moisture content, ash content, volatile matter content during the heating process, bound carbon and heating value. Research on the production of charcoal briquettes was carried out using bagasse waste with variations in the addition of tapioca adhesive and molasses. It can be concluded that the best quality briquettes are A1 briquettes, namely bagasse briquettes with 0.5 gram of adhesive drops, which are close to the standard criteria of briquettes, namely the highest calorific value, lowest moisture content, lowest ash content and lowest volatile matter content.